2021
DOI: 10.3390/cancers13153723
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Variation in Radiomic Features of Head and Neck Squamous Cell Carcinoma and Its Impact on Machine Learning Models

Abstract: Current radiomic studies of head and neck squamous cell carcinomas (HNSCC) are typically based on datasets combining tumors from different locations, assuming that the radiomic features are similar based on histopathologic characteristics. However, molecular pathogenesis and treatment in HNSCC substantially vary across different tumor sites. It is not known if a statistical difference exists between radiomic features from different tumor sites and how they affect machine learning model performance in endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Specifically, HPV status is missing in 55% of the sample, with 175 missing from the LHC, 3 from the OPC and 155 from the OSCC, that is, about 95% of the total observations with site OSCC (see Figure 2). Note that HPV is considered an important predictor for lymph node metastasis (Liu et al, 2021). Therefore, given the disproportionate missingness structure, an independent site-stratified inference and prediction can result in severe loss of information and low statistical power.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, HPV status is missing in 55% of the sample, with 175 missing from the LHC, 3 from the OPC and 155 from the OSCC, that is, about 95% of the total observations with site OSCC (see Figure 2). Note that HPV is considered an important predictor for lymph node metastasis (Liu et al, 2021). Therefore, given the disproportionate missingness structure, an independent site-stratified inference and prediction can result in severe loss of information and low statistical power.…”
Section: Datamentioning
confidence: 99%
“…Medical imaging analysis plays a central role in the personalized treatment decisions and outcome prognosis of cancer patients. For example, in head and neck squamous cell carcinoma (HNSCC), a heterogeneous malignancy constituting more than 95% of head and neck cancers (Liu et al 2021), clinical management is based on manually measured features such as the tumour size, local disease extension and presence of distant metastasis (Deschler & Day, 2008). Unfortunately, there is a considerable time cost to collecting these semantic features, since they must be quantified by a trained radiologist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2c shows an example of the SSIM map (left) and its corresponding histogram (right). Six commonly used features, that is, mean, median, moment (second order), skewness, kurtosis, full width at half maximum (FWHM), 24,25 were extracted from the SSIM maps for all daily MRI sets.…”
Section: Ssim (X Y) = [L (X Y)]mentioning
confidence: 99%
“…A recent study investigated the site-specific variation in radiomics features of head and neck squamous cell carcinoma [8], and several further studies demonstrated the ability of radiomics features to perform histological subtype classification among several cancer types [9][10][11]. In their limited to head and neck cancer, Liu et al [8] thus suggested that the tumour site should be considered when developing radiomics-based models.…”
Section: Introductionmentioning
confidence: 99%